2022
DOI: 10.1159/000526319
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Approach in Chronic Dialysis Patients with SARS-CoV-2: ATA or PMMA Dialyzers?

Abstract: <b><i>Introduction:</i></b> High-flux hemodialysis membranes may modulate the cytokine storm of SARS-CoV-2, but their impact on chronic hemodialysis (CHD) patients is unknown. The aim of the study was the evaluation of asymmetric cellulose triacetate (ATA) and polymethylmethacrylate (PMMA) dialyzers on inflammatory markers and clinical outcomes in CHD patients with SARS-CoV-2. <b><i>Methods:</i></b> A prospective, observational study on CHD patients with SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…There was a tendency for lower HNA-1/HNA-2 fractions after haemodialysis treatment with a PMMA or CTA dialyzer compared to polysulfone dialyzers. These results are limited by the low number of patients in these subgroups, but in line with the findings of a larger prospective observational trial by Donati et al [ 25 ]. Further, the PMMA and CTA based dialyzers do not contain PVP.…”
Section: Discussionsupporting
confidence: 84%
“…There was a tendency for lower HNA-1/HNA-2 fractions after haemodialysis treatment with a PMMA or CTA dialyzer compared to polysulfone dialyzers. These results are limited by the low number of patients in these subgroups, but in line with the findings of a larger prospective observational trial by Donati et al [ 25 ]. Further, the PMMA and CTA based dialyzers do not contain PVP.…”
Section: Discussionsupporting
confidence: 84%
“…The use of filters by asymmetric cellulose triacetate (ATA) was compared to filters by polymethylmethacrylate (PMMA). Using a multivariate logistic regression model, the authors concluded that ATA favoured the retention of IL-6 [ 20 ]. In the second small-scale randomized trial, 15 patients underwent HD using medium cut-off (MCO) membranes and were compared to 14 patients who underwent HD using filters by PMMA.…”
Section: Discussionmentioning
confidence: 99%
“…Other group of research on reducing IL-6 levels in hemodialyzed is based on choosing adequate dialysis technique. Donati et al found that asymmetric cellulose acetate (ATA) dialyzers were superior when it comes to removing IL-6 over polymethylmethacrylate (PMMA) dialyzers [33]. A randomized controlled trial by Weiner et al aimed to examine the efficacy of medium cut-off dialyzers vs. standard high-flux dialyzers in removal of uremic toxins during four-and 24-week period.…”
Section: Discussionmentioning
confidence: 99%